Quorum sensing: Little talks for an effective bacterial coordination - Turan, Nouha Bakaraki; Chormey, Dotse Selali; Buyukpinar, Cagdas; Engin, Guleda Onkal; Bakirdere, Sezgin (ELSEVIER SCI LTD, 2017)
The bacterial communication through signaling molecules termed quorum sensing has gained a lot of attention due to its applicability to different fields of study. Quorum sensing regulates several bacterial activities such as biofilm formation, antibiotic resistance, bioluminescence and bacterial virulence. These coordinated activities are only realized when the bacterial population reaches a high population density. The signaling molecules used in quorum sensing occur at very low concentrations which call for very sensitive methods for their identification and characterization. Many studies have been performed on the use of inhibitors in attempt to disrupt quorum sensing and consequently alleviate its negative effects. This article gives a description of the types of auto-inducers involved in quorum sensing and the fields of study they greatly affect especially the environmental one. It also covers types of analytical sample preparation and detection methods, and different types of inhibitors used for quorum quenching. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Signaling molecules; Quorum sensing; Bacteria; Biofilm; Quorum quenching; GRAM-NEGATIVE BACTERIA; TO-CELL COMMUNICATION; L-HOMOSERINE LACTONES; SOLID-PHASE MICROEXTRACTION; WASTE-WATER TREATMENT; PSEUDOMONAS-AERUGINOSA; QUENCHING BACTERIA; BIOFOULING CONTROL; MEMBRANE BIOREACTOR; MASS-SPECTROMETRY; Chemistry